Linguistic evolution of views on the notion of concept as a unit of a conceptual picture of the world (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article reviews the evolution of linguistic views of national and foreign linguists on the notion of conceptual and linguistic picture of the world, concept. Basic and non-basic conceptual point of intersection of the concepts and language pictures of the world are considered. A generalized interpretation of the notion of «conceptual picture of the world», «language world», «concept» is offered.